Konservasi Sumber Daya Air Melalui Penanaman Tumbuhan Bergad Di Desa Menawan Guna Pelestarian Lingkungan - Mukaromah, Ulfatul; Nabila Anansyah, Farah; Muhammad Firdaus, Tegar; Nanda Pratama, Raka; Christian Mercyus Silalahi, Andre (Universitas Negeri Semarang, 2025)
Menawan Village is experiencing a decline in the quality and quantity of water resources due to environmental damage caused by climate change and human activities. Responding to this challenge, the UNNES GIAT 9 Team collaborated with Karang Taruna Wirabakti and the UNISNU KKN Team to carry out environmental conservation activities aimed at maintaining and restoring the ecosystem around the Lengkong spring and the Guyangan Sokokaleh Pine Forest. The object of service is the people of Menawan Village, especially the younger generation, who are actively involved in this activity. The service method used is a participatory approach, which involves coordination and preparation, planting bergad plants, education and community empowerment, as well as monitoring and evaluation. The results of the activity show that planting bergad plants around water sources has succeeded in increasing water absorption capacity and preventing erosion, so it is hoped that it will be able to improve the quality and quantity of available water. Apart from that, this activity also increases public awareness, especially the younger generation, of the importance of protecting the environment and natural resources in a sustainable manner.